PENGARUH MODEL PEMBELAJARAN RADEC BERBASIS LITERASI DIGITAL TERHADAP KEMAMPUAN MEMBACA KRITIS DAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Syarifah Rida Nura, - (2020)
This research is motivated by the low ability of critical reading and critical thinking of students in elementary schools. This study aims to determine the effect of the digital literacy-based RADEC learning model on the critical reading and critical thinking skills of elementary school students. This study uses a quantitative approach, a quasi- experimental method with a nonequivalent control group design. This research was conducted in one of the State Elementary Schools in Aceh Besar Regency, involving 44 grade 5 students who were taken randomly. The research instruments used were multiple choice tests for critical reading skills, essay tests for critical thinking skills, and observation sheets for learning activities using the RADEC learning model to assess teacher performance and student abilities. The test was carried out in two stages, namely the pretest was given before the treatment and the posttest was given after the treatment. This research uses t test (independent sample t-test) and N-gain test. The test results on the ability to read critically and think critically obtained a significance value (2-tailed) of 0.000 < 0.05. Proving that the digital literacy-based RADEC learning model has a significant effect on students' critical reading and critical thinking skills. The RADEC learning model based on digital literacy in the process of teaching and learning activities makes students more active so that they can improve students' critical reading and critical thinking skills.